Stochastic game strategies and their applications - Chen, Bor-Sen ([Place of publication not identified] : CRC Press, 2019)
Game theory involves multi-person decision making and differential dynamic game theory has been widely applied to n-person decision making problems, which are stimulated by a vast number of applications. This book addresses the gap to discuss general stochastic n-person noncooperative and cooperative game theory with wide applications to control systems, signal processing systems, communication systems, managements, financial systems, and biological systems. H
Part I: General Theory of Stochastic Games Chapter 1: Introduction Chapter 2: Introduction to Stochastic Games in Linear Stochastic Systems Chapter 3 Introduction to Stochastic Games in Nonlinear Stochastic Systems Part II: Stochastic Game Strategies in Control System Designs Chapter 4: Robust Adaptive Tracking Control Design of Robot Systems under Parameter Perturbation and External Disturbance: A Minimax H
OCLC-licensed vendor bibliographic record.
Keywords: MATHEMATICS / Applied; MATHEMATICS / Game Theory; TECHNOLOGY / Electricity; Game theory